2007
DOI: 10.1037/0021-843x.116.4.645
|View full text |Cite
|
Sign up to set email alerts
|

Linking antisocial behavior, substance use, and personality: An integrative quantitative model of the adult externalizing spectrum.

Abstract: Antisocial behavior, substance use, and impulsive and aggressive personality traits often co-occur, forming a coherent spectrum of personality and psychopathology. In the current research, the authors developed a novel quantitative model of this spectrum. Over 3 waves of iterative data collection, 1,787 adult participants selected to represent a range across the externalizing spectrum provided extensive data about specific externalizing behaviors. Statistical methods such as item response theory and semiparame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

60
889
1
16

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 753 publications
(966 citation statements)
references
References 127 publications
(151 reference statements)
60
889
1
16
Order By: Relevance
“…Further, the effect of reduced responsiveness to reward is consistent with data from patient populations (Barkley et al, 2001;Demurie et al, 2012;White et al, 2014). Regarding the scale measure of disinhibition we used, this measure was carefully designed to index liability toward externalizing problems (Krueger et al, 2007;Patrick et al, 2013), and prior research has shown that scores on this scale covary substantially with interview-assessed externalizing symptoms-largely as a function of shared genetic influences that covary in turn with brain response . As such, this scale measure provides an effective vehicle for bridging between brain response measures and clinical problems .…”
Section: Discussionmentioning
confidence: 50%
See 2 more Smart Citations
“…Further, the effect of reduced responsiveness to reward is consistent with data from patient populations (Barkley et al, 2001;Demurie et al, 2012;White et al, 2014). Regarding the scale measure of disinhibition we used, this measure was carefully designed to index liability toward externalizing problems (Krueger et al, 2007;Patrick et al, 2013), and prior research has shown that scores on this scale covary substantially with interview-assessed externalizing symptoms-largely as a function of shared genetic influences that covary in turn with brain response . As such, this scale measure provides an effective vehicle for bridging between brain response measures and clinical problems .…”
Section: Discussionmentioning
confidence: 50%
“…Trait disinhibition was operationalized by scores on a scale measure consisting of 30 items from the Externalizing Spectrum Inventory (Krueger et al, 2007). For details regarding scale content and properties, see Supplementary Methods.…”
Section: Trait Disinhibition Measurementioning
confidence: 99%
See 1 more Smart Citation
“…5,6,8 In general terms, traits related to appetitive and unconstrained behavioral tendencies have been identified in the personality profile of subjects with harmful patterns of substance use and general externalizing problems. [9][10][11][12] Among the constellation of traits related to appetitive and unconstrained dispositions, two have gained particular attention in the literature: novelty seeking (NS) 8 and sensation seeking (SS). 13 Both of these traits have been considered major personality variables when related to alcohol and drug consumption for empirical and conceptual reasons.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] These efforts have been directed at addressing inherent limitations associated with pervasive clinical heterogeneity and diagnostic comorbidity, [5][6][7][8] along with the fact that covariance patterns among differing psychopathologies and temperament/personality traits are not addressed by dominant classification systems of mental disorders. 9,10 In response to these limitations, different researchers have modeled the underlying structure of common psychiatric conditions to characterize diagnostic overlap using structural equation modeling techniques.…”
Section: Introductionmentioning
confidence: 99%